Copper-catalyzed meta-selective arylation of phenol derivatives: an easy access to m-aryl phenols - Maraswami, Manikantha (2022)
Achieving selective meta-functionalization of phenols is a significant challenge. Accessing such compounds generally needs elevated temperature or incorporation of complex templates. Here, we report a general approach to achieve meta-arylated phenols with a simple and common directing group. This coppercatalyzed protocol proceeds with complete meta-selectivity and tolerates a variety of functional groups in both coupling partners. Computational studies have revealed that the reaction proceeded via a Heck-like pathway.